2021
DOI: 10.1590/1806-9061-2020-1302
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Circulatory Adiponectin and Plasma Variables in Broilers

Abstract: Adipokines serve as a human clinical biomarker and they regulate mammalian metabolic functions. Research on adipokine regulation of metabolic function in avian species is limited. The current study is to investigate the profile of plasma adiponectin and several biochemical variables in broilers, to establish the pattern of development.A total of one hundred and fifty-two 1-day-old Arbor Acres broilers were separated by different gender and homogenously divided into 2 groups (male and female), with 6 replicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, our previous research also confirmed that HMW ApN was highly correlated with age in a positive fashion in both sexes (Chen et al, 2021). Although we know some characteristics of chicken ApN, current research does not have an in-depth understanding of its physiological functions.…”
Section: Introductionmentioning
confidence: 72%
“…In addition, our previous research also confirmed that HMW ApN was highly correlated with age in a positive fashion in both sexes (Chen et al, 2021). Although we know some characteristics of chicken ApN, current research does not have an in-depth understanding of its physiological functions.…”
Section: Introductionmentioning
confidence: 72%